Übersetzen ohne Kenntnis der fremden Sprache. Rainer Maria Rilke und die „portugiesischen“ Sonette von Elizabeth Barrett Browning - Erich Unglaub (Slovo a Smysl, 2020)
Professional practice seems to preclude translating texts from a language over which the translator has not achieved mastery. However, 20th century German literature has at least two prominent examples of such cases. Rainer Maria Rilke translated the sonnets of the English poet Elizabeth Barrett Browning and Karl Kraus the Sonnets of Shakespeare. Looking to Rilke, it is apparent that such a project can succeed under the right conditions. Collaborators and friends provided preliminary and prose versions, making possible a translation process analogous to the act of creation. Rilke illustrates this process with Stendhal’s picture of ‘crystallization’. Meanwhile, the creation of the collection Sonnets from the Portuguese reveals some questions and problems associated with the act of translation, also evident in the title and authorship of the publications.